Characteristics of cell adhesion molecules expression and environmental adaptation in yak lung tissue - Wang, Huizhen; Huang, Nating; Tan, Minglu; Zhang, Xun; Chen, Jiarui; Wei, Qing (Scientific reports, 2025)
Cell Adhesion Molecules (CAMs) play a crucial role in regulating immune responses and repairing damage caused by hypoxia. However, the relationship between the expression characteristics of CAMs in yak lung tissues and their adaptation to the plateau environment remains unclear. To address this question, we compared lung tissues from yaks and cattle at the same altitude. After digesting the lung tissues with trypsin or Type I collagenase for varying durations, we observed that fewer cells were isolated from yak tissues compared to cattle. RNA sequencing (RNA-seq) analysis revealed that the Differentially Expressed Genes (DEGs) in lung tissues of yaks and cattle were significantly enriched in cell adhesion-related pathways. Quantitative real-time PCR (qRT-PCR) further identified changes in the expression levels of five distinct types of CAMs. Among these, the cadherin family ( CDH1 , CDH2 , CDH11 , PCDH12 , CD34 ) exhibited significantly higher expression in yaks than in cattle. These cadherins play a critical role in regulating lung inflammation and maintaining the alveolar-capillary barrier, thereby ensuring the structural stability of the lungs. Immunohistochemical staining demonstrated that the expression patterns of cell adhesion-related proteins (CDH1, CDH11, ITGB6, SELP, CD44) were largely consistent with the qRT-PCR results. In conclusion, compared to cattle, the enhanced cell adhesion capacity of yak lung tissues contributes to their superior adaptation to the harsh plateau environment.